Effects of Chronic Physical Exercise or Multicomponent Exercise Programs on the Mental Health and Cognition of Older Adults Living in a Nursing Home: A Systematic Review of Studies From the Past 10 Years - Da Silva, Jason Leonardo; Agbangla, Nounagnon Frutueux; Le Page, Christine; Ghernout, Wahiba; Andrieu, Bernard (Frontiers in Psychology, 2022)
Nursing homes for the elderly provide holistic care that integrates several interventions, including physical exercise. The aim of this systematic review is to summarize the effects of physical exercise or multicomponent exercise programs on the mental health (well-being, anxiety and depression) and cognitive functions of older adults with/without dementia who live in a nursing home and do/do not require wheelchair assistance. To this end, PubMed, PsycInfo and Web of Science were used to identify clinical trials and randomized controlled studies conducted during the period January 2011 to December 2021. After selecting articles according to the PRISMA standards, the data extraction and methodological quality assessment of the eligible studies were performed individually by two reviewers and then pooled together. The synthesis of the studies showed that physical exercise or multicomponent exercise programs had a beneficial effect on mental health and cognitive functions. However, this effect was more common among older adults without dementia, compared to their counterparts who have dementia or use wheelchairs. The explanatory mechanisms, lack of benefits from physical exercise and the need to standardize methods were discussed in this regard. Finally, new research perspectives were proposed.